Metode Prototipe Untuk Sistem Informasi Inventori Berbasis Web - Nurhadi Nurhadi; Annisa Assajdah (Politeknik Kampar, 2023)
Warehouse has an important role to support the company's success in achieving its goals, because in this part of the warehouse there is a process of processing input into output. Some Warehouses in a data processing company still use the manual method, namely by filling in the form provided by the company and then storing it in a folder for archiving. This system is good, but there are still perceived weaknesses, including if it is required to quickly find the data needed it is rather difficult, because you have to search for one by one the archives that have been stored, it will take quite a long time, so a lot of time is wasted. Another problem is that the possibility of data or archives being lost or damaged is still very high, with this error the company will suffer losses, that is what must be avoided. In this study the authors created an Inventory Information System as a basis which aims to provide convenience in data processing, especially in warehouses. an information system that is made web-based so that the system can be integrated with other parts, and in developing this information system a prototype method is used so that this system can actually be used by users and can be used easily because in its development it uses a prototype method which involves user.